Dataset of cone opponent mechanisms and spectral tuning in non-primate vertebratesOSF - Carlay L. Teed; Samuel Hartzler; Esteban Fernández-Juricic (Data in Brief)
Cone and spectral opponency are fundamental to colour processing in many species and are well studied in primates. The data required to make interspecific comparisons of the neural mechanisms associated with colour processing is spread across a broad body of literature reaching back to the 1950ʼs across four retinal cell types and multiple brain regions. We aimed to produce a comprehensive dataset of all known cone opponent cells in non-primate vertebrates in image forming visual pathways. We completed a systematic literature search of two databases, Web of Science and Scopus, following PRISMA guidelines. From the data collected, we produced three datasets. One dataset contains cone opponency data that indicates which photoreceptors drive cell light responses. The second dataset contains spectral opponency data that represents the cell electrical responses to different wavelengths of light. Additionally, we developed a third database of photoreceptor data for the species for which cone or spectral opponency was reported to supplement the first two. These datasets will provide a synthesis of the data in the field of colour processing, can be used for interspecific and intraspecific meta-analyses, and can provide a starting point for understanding neural mechanisms behind wavelength comparisons in non-primate vertebrates.